An Integrated Framework for Efficient Implementation Of Enterprise Systems (International Journal of Engineering and Computer Science, 2017)
The today’s enterprise systems usually form a system of sub-applications, each being responsible for aparticular functionality. Hence, the design and maintenance of such a complex system is not a simple task.In addition, the user requirements can change and the affected parts need to be identified and evolved.Similarly, new components or even whole system may need to be integrated. Companies in order to buildand sustain competitive advantage have to rely more and more on their IT systems in virtually every aspectof their business operations. In spite of this and despite their critical operational, tactic and strategic role,many new and old IT systems have either not offered what they were created for, or have failed outright.Many of these failures and inadequacies result from a poorly executed development process. Thedevelopment processes used employ either inadequate development models or flawed implementation due, inpart, to the lack of proper frameworks and effective collaborative mechanisms between the development andintegration functions. This puts forward high requirements on information systems and in turn, raises agreat challenge to software developers. In order to build and sustain such systems, an integrated frameworkis needed for building and implementing business applications to automate business processes and supportthe business functions of the enterprise. The method adopted for the design is the Iterative Design Method.An integrated architecture framework was developed as a tool for efficient implementation of enterprisesystem as the end objective. Comprehensive system frameworks are necessary to capture the entirecomplexity of such systems. The architecture framework provides the conceptual foundation that includesBusiness, Information, information system, infrastructure and governance and security views necessary forbuilding and managing the integral business system and all its components and also provides an integrateddescription of enterprise information systems in terms of the instantiation of the architecture framework.